Understanding Volunteer Management in 4-H - Bryan D. Terry; Rick Godke; Bill Heltemes; Lori Wiggins (EDIS)
This document is 4-H 6.3, one of a series by Bryan D. Terry, Rick Godke, Bill Heltemes, and Lori Wiggins that has been published by the UF 4-H and Youth Development Program, October 2010.